Inverse relationship between fasting direct bilirubin and metabolic syndrome in Korean adults - Hwang, Hee-Jin; Kim, Sang-Hwan (Clinica chimica acta, 2010)
Studies on the effects of bilirubin on cardiovascular disease have typically focused only on total serum bilirubin composed with direct bilirubin plus indirect bilirubin. In this study, we examined which type of fasting bilirubin is more associated with the metabolic syndrome (MS). Five thousand six hundred and fifty-four individuals who visited the Center for Health Promotion for a periodic medical health check-up were screened for inclusion in the study. We excluded subjects who had a chronic viral liver disease, an alcoholic liver disease, or an abnormal liver function defined as a serum aspartate aminotransferase or alanine aminotransferase > 100 IU/l, a gamma glutamyltransferase > 100 IU/l, or a fasting total bilirubin level > 3 mg/dl. In men, only fasting direct bilirubin levels decreased with an increase in the number of MS components (p = 0.001). However, all three types of fasting bilirubin decreased when the subjects had more components of MS (p < 0.001) in women. Both in men and women fasting direct bilirubin levels were related with the MS (p for trend = 0.003 in men and < 0.001 in women) after the adjustments for age, body mass index, smoking, alcohol drinking, exercise habits, and presence of fatty liver. The odds ratio (95% confidence interval) of MS for each fasting direct bilirubin quartile was 0.88 (0.59–1.29), 0.63 (0.42–0.95), 0.61 (0.38–0.97) in men, and 0.66 (0.50–0.87), 0.52 (0.35–0.78), 0.27 (0.12–0.59) in women, respectively. However, fasting total and indirect bilirubin levels were related with the MS in women, but not in men. Our findings suggest that MS is more related to the fasting direct bilirubin in Korean adults than the other types of fasting bilirubin.